Reflections on the efficacy of the Human Resource Management strategies of international organisations, regarding expatriation, repatriation and relocation - Tivey, Laura (2008)
The paper reviews the academic literature on the requirements that need to be considered by organisations, when pursuing expatriation and repatriation of employees. Through a survey posted on the internet (during 2008) an up-to-date assessment of the current situation was attempted. Although there were a limited number of respondents covering a wide range of expatriation experiences, the paper reports the continuing failure of HR departments and the organisations in question, to address the needs of expatriates and their dependents before, during and after their tenure abroad. This is found to jeopardise the successful and efficient integration of the employee into the foreign assignment.